Дослідження мікроструктури і твердості дослідних рейкових сталей в литому стані, після гарячої пластичної деформації і термічної обробки - Бабаченко, Олександр; Кононенко, Ганна; Подольський, Ростислав; Сафронова, Олена (Physico-technological Institute of Metals and Alloys, 2023)
The mechanical properties of railroad rails depend on the chemical composition, the elaboration of the cast structure by metal pressure treatment, as well as the heat treatment of the finished rails. The aim of this work is to study the effect of hot plastic deformation (hereinafter HPD) and heat treatment (hereinafter HT) on the change in the structure of the cast state in relation to its initial chemical heterogeneity. The general theoretical conclusions of this work were obtained on the basis of an analysis of literary sources, as well as many years of research on wheel products. These results complement the existing understanding of structural heredity in metals and alloys. The chemical composition of experimental steels for railroad rails has been developed and ingots weighing up to 10 kg have been smelted under laboratory conditions. The study of the microstructure was carried out and the hardness of the experimental steel was determined on samples of 70x70x80 mm in size, cut from ingots of laboratory rail heats. It was processed in laboratory conditions in two modes: 1 – HPD with a sediment of 50 % after heating to 1250 ± 10 °С; 2 – normalization (austenitization at 900 ± 10 °C, air cooling at a rate of 5.1 °C/s) after HPD. In the study of the cast state of experimental rail steels (RST), it was found that it is austenite dendrites enriched with impurity elements. The effect of hot plastic deformation and heat treatment on the structure and properties of a cast test steel for railroad rails has been studied. The positive effect of deformation and subsequent heat treatment on the mechanical properties of experimental steels was established: after hot plastic deformation, in comparison with the cast state, the increase in hardness was ≈ 14.1 %; after hot plastic deformation with subsequent heat treatment, the increase in hardness was ≈ 39.4 %. The influence of the primary dendritic structure of the investigated steel on its final pearlite structure in the cast state has been established.